Analysis of Clostridium difficile Isolates from Nosocomial Outbreaks at Three Hospitals in Diverse Areas of Japan - Kato, Haru (American Society for Microbiology, 2001)
Clostridium difficile isolates recovered from patients with C. difficile-associated diarrhea (CDAD) at three hospitals located in diverse areas of Japan were analyzed by three typing systems, PCR ribotyping, pulsed-field gel electrophoresis (PFGE), and Western immunoblotting. At the three hospitals examined, a single PCR ribotype strain (type smz) was predominant and accounted for 22 (65%) of 34, 18 (64%) of 28, and 11 (44%) of 25 isolates, respectively. All of the 51 isolates that represented PCR ribotype smz were nontypeable by PFGE because of DNA degradation. Since the type smz strain did not react with any of the antisera against 10 different serogroups (A, B, C, D, F, G, H, I, K, and X), we prepared a new antiserum against a type smz isolate. All 51 type smz isolates presented identical banding patterns, reacting with the newly prepared antiserum (designated subserogroup JP-0 of serogroup JP). These results were compared with those of a strain from a hospital outbreak that occurred in New York, which has been identified as type J9 by restriction enzyme analysis and type 01/A by arbitrarily primed PCR but was nontypeable by PFGE because of DNA degradation. This strain was reported to be epidemic at multiple hospitals in the United States. The J9 strain represented a PCR ribotype pattern different from that of a type smz strain and was typed as subserogroup G-1 of serogroup G by immunoblot analysis. A single outbreak type causing nosocomial CDAD in Japan was found to be different from the strain causing multiple outbreaks in the United States, even though the outbreak strains from the two countries were nontypeable by PFGE because of DNA degradation.